Tiga Kelompok Pengunjung berdasarkan Durasi Kunjungan dan Karakteristik Taman - Jasmine C U Bachtiar; Hanson Endra Kusuma (http://arl.faperta.ipb.ac.id/, 2019)
The characteristics of urban parks can attract and makes visitors want to stay longer. The long duration of the visit in the urban park can increase visitor’s attitude toward a place. The longer they stay, the stronger the sense of belonging they have in that place. This current study wants to find out how the grouping of visitors in the urban park was based on the duration of the visit and the characteristics of the park. Data collection was carried out by distributing online questionnaires and the data of 211 respondents was processed for this study. Data was processed by explanatory qualitative method, with open coding, axial coding, and selective coding analyses. The result showed that there were three large groups of visitors in the park, who had different level of attitudes toward urban parks, namely relaxation, escape, and audience group. Audience group was assumed having the highest level of attitude toward urban parks than others. In order to increase the duration of the visit, the urban parks require attractions that are in demand by the audience. Keywords: duration of the visit, place characteristics, sense of place, urban parks